2018
DOI: 10.2147/nss.s125839
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sleep disorders in patients with chronic kidney disease

Abstract: Kidney disorders have been associated with a variety of sleep-related disorders. Therefore, researchers are placing greater emphasis on finding the role of chronic kidney disease (CKD) in the development of obstructive sleep apnea and restless legs syndrome. Unfortunately, the presence of other sleep-related disorders with CKDs and non-CKDs has not been investigated with the same clinical rigor. Recent studies have revealed that myriad of sleep disorders are associated with CKDs. Furthermore, there are a few n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 93 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…Significance levels were determined at p ≤ .05. LCA was estimated using Mplus V 8.1 (Muthén & Muthén, 2018); all other analyses were conducted in StataIC 15 (StataCorp., College Station, TX).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significance levels were determined at p ≤ .05. LCA was estimated using Mplus V 8.1 (Muthén & Muthén, 2018); all other analyses were conducted in StataIC 15 (StataCorp., College Station, TX).…”
Section: Discussionmentioning
confidence: 99%
“…Variable-centered approaches to clustering, which seek to identify relationships among symptoms and quantify the patient's symptom experience, have been employed in patients with ESRD (Amro et al, 2015;Yu, Huang, & Tsai, 2012). Fatigue (Jhamb et al, 2013;Rodrigue et al, 2011), sleep disturbance (Nigam, Camacho, Chang, & Riaz, 2018), depression/anxiety (Assari & Burgard, 2015), pain (Song, Paul, Ward, Gilet, & Hladik, 2018), and gastrointestinal symptoms (Zhang, Bansal, Go, & Hsu, 2015) are among the most common co-occurring symptoms in CKD (Lockwood et al, 2019). Although variable center approaches are useful in examining relationships among homogeneous populations (Conley, 2017), variable-centered approaches to clustering symptoms are complicated by difficulty interpreting symptom clusters due to heterogeneity of symptom response patterns, thereby limiting their clinical utility (Conley, 2017;Lockwood et al, 2019;Ryan et al, 2019).…”
mentioning
confidence: 99%
“…Many a time, healthcare professionals fail to recognize the kind of sleep disorder unless they know the common sleep-related issues in accordance with chronic kidney disease (CKD) [1]. Various sleep disorders are associated with CKD, which include insomnia, sleep-related breathing disorders, hypoventilation, central sleep apnea, central disorders of hypersomnolence, circadian rhythm sleep-wake disorders, parasomnias, and sleep-related movement disorders [2].…”
Section: Introductionmentioning
confidence: 99%
“…Deleterious adverse complications related to CKD and the limited feasibility of currently known therapies serve as a motivation to seek a novel, more effective therapeutic strategy for the prevention or delay of renal injury and of the progression to CKD [ 23 , 24 , 25 ]. Previous studies have suggested that patients with CKD experience sleep impairments, such as obstructive sleep apnea and restless leg syndrome, and that progression to CKD or end-stage renal disease (ESRD) may be correlated with the development of various sleep disorders [ 26 , 27 ]. Similarly, our recent study showed that melatonin ( N -acetyl-5-methoxy tryptamine) secreted by the pineal gland reduces MSCs senescence induced by uremic toxins commonly accumulated in patients with CKD, which suggested that it may offer a potential intervention to enhance MSC-derived therapy for the prevention of CKD progression [ 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%